Didactics of Electrical Engineering and Its Components in the Context of Digitalization of Education - SERAFÍN, ČESTMÍR (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2023)
Didactics is defined as the theory of education. It deals with the specific forms, procedures and goals of teaching that a teacher implements with his/her students. As such, it is an integral part of pedagogy. Since the forms, procedures and objectives of teaching vary in their specificity for the different fields, disciplines and subjects of education, this specificity is reflected in the disciplinary or subject didactics. The latter thus deal with the processes of teaching and learning with regard to subject-specificity and specificity. The article is thematically devoted to the area of subject or subject didactics, specifically didactics of electrical engineering, which is of particular importance for vocational technical education, as it forms a key part of it both in practice and in the preparation of teachers of such disciplines. The article also presents some of the results of the author’s research from recent years, which focuses specifically on the areas of modern technologies and their impact on the teaching process, especially in electrical engineering-oriented teaching subjects; tools for developing technical but also digital literacy are presented.